2017
DOI: 10.1007/s11356-017-8897-5
|View full text |Cite
|
Sign up to set email alerts
|

User preferences and water use savings owing to washbasin taps retrofit: a case study of the DECivil building of the University of Aveiro

Abstract: During the last decades, achieving water efficiency in buildings has increasingly become an important challenge in the scope of sustainability. Water consumption is directly related to individual conduct. Despite the various technological improvements in fixtures and appliances, their performance will be influenced by human preferences and behavior. As a result, the potential for effective water consumption saving is influenced by behavior change as well as water-efficient fixtures and appliances. This work ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
7
1
2
Order By: Relevance
“…They concluded that satisfaction and usage water flow have a spurious correlation relationship, and this was also confirmed by this study. But the findings contradict Meireles et al (2018) study of taps, which found that female participants were more conservative in estimating their use duration and therefore water use compared with the male participants. This study did not find such gender correlations; instead, the shower durations varied more in line with the use, and effectiveness of the showerheads to meet the participant's requirements and levels of experiential satisfaction, relative to the purpose of the shower.…”
Section: Discussioncontrasting
confidence: 83%
“…They concluded that satisfaction and usage water flow have a spurious correlation relationship, and this was also confirmed by this study. But the findings contradict Meireles et al (2018) study of taps, which found that female participants were more conservative in estimating their use duration and therefore water use compared with the male participants. This study did not find such gender correlations; instead, the shower durations varied more in line with the use, and effectiveness of the showerheads to meet the participant's requirements and levels of experiential satisfaction, relative to the purpose of the shower.…”
Section: Discussioncontrasting
confidence: 83%
“…The obtained results allowed them to determine the trends in cold-and hot-water consumption, as well as to estimate the energy required for water heating. Meireles 105 Levels 5 and 6 (CHS) et al [45] carried out a study on water savings for washbasin mixers equipped with different aerators. The authors also analysed how the preferences of users influence the level of water consumption savings and whether the application of water-saving faucets is fully utilized.…”
Section: Methodsmentioning
confidence: 99%
“…The water reducers efficiency will depend on the users' behaviour. Meireles et al [6] found that reduction in water consumption associated to the installation of water reducers in the DECivil building was lower than the reduction of water discharge due to user's behaviour adjustment to the lower water discharge (no change in the duration of operation per push was introduced).…”
Section: Water Consumption Reduction Potentialmentioning
confidence: 99%